Methodology for applying innovative and pedagogical technologies in the development of creativity abilities of students through the national dance tool (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article will talk about the main features of the musical culture of Uzbekistan and Uzbek dance art. Opinions and information about the process of historical development of musical art, musical life, Uzbek national dance, how to use innovative technologies in order to develop interests in this art in students are described. Dance is considered a type of art, in which movements, compositions are made up of a certain rhythm and tempo, performed through emotional impressions that arise on the basis of the labor process of mankind and changes in domestic life. Of course, there are directions in which the dance art of each people, dance traditions, style of performance, visual means are performed in the direction of melody and music. Today, there is a growing need for students to spend their extracurricular time meaningfully. The need lies in improving the methods of performance skills in the development of creativity, the continuity of the theory and practice of performance skills and the need to know the principles of didactics, such as science, systemicity, sequence and consistency, enriching them with unbiased conclusions. Taking into account the important features of didactics, as well as other subjects, in the educational process, improving the pedagogical methodology of teaching dance art to young people, the student assumes the correct orientation of the students ' specific interest and creativity in dance art.